Testing market efficiency in Malaysia's large, medium and small stock market indices - Heng, Cheat Yee (2020)
As if random walk does not exist and the market is inefficient in weak form, then technical analysis used by technical analysts would grant them profitability. Therefore, it is crucial to determine whether the securities or the market price follow random walk or not. This paper examines whether Malaysia large, medium and small stock market indices are efficient and follow random walk or not. Daily and weekly return series from 31st October 2014 to 31st October 2019 are collected and analysed by using the Bloomberg Terminal. KLCI, FBM70, FBMSC and MESDAQ are proxy as the stock market indices with different categories of capitalizations. In order to examine the existence of random walk and market efficiency, multiple tests are used to achieve the research objective where are normality test, autocorrelation test, run test, unit root tests and the variance ratio test. The result finding indicates that in overall, despite of different size of stock market exhibits different characteristics, all the four examined stock market indices or benchmark with different categories of capitalization are not likely to follow random walk according to the empirical evidence. Therefore, we can conclude that Malaysia large, medium and small capitalization stock market indices do not follow random walk and are inefficient in weak form market efficiency. The stock market might be predictable and so there might be feasibility to take advantage of the price movement. Therefore, it is feasible for investors and traders to earn abnormal return in Malaysia stock market by utilizing the historical information.